2017
DOI: 10.1016/j.foodchem.2016.11.154
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rocket salad phytochemicals within the commercial supply chain: Glucosinolates, isothiocyanates, amino acids and bacterial load increase significantly after processing

Abstract: HighlightsGlucosinolates, isothiocyanates and amino acids increase significantly over time.Glucoraphanin is not significantly affected by harvesting and processing.Sulforaphane significantly increases after processing in E. sativa cultivars.Bacterial load of leaves is correlated with glucosinolate and amino acid abundance.Commercial processing may increase the nutritional value of E. sativa to consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 40 publications
1
49
4
1
Order By: Relevance
“…In agreement with previous studies [1,11], isothiocyanates were lost during storage. However, this finding contrasts with work in Eruca sativa where isothiocyanates rose during storage [38] and could relate to differences between the two rocket salad species. The differential changes in response to the different stress treatments is consistent with the subtle changes induced by storage at different temperatures [11] and effects of wounding on the release of VOCs [20,39].…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with previous studies [1,11], isothiocyanates were lost during storage. However, this finding contrasts with work in Eruca sativa where isothiocyanates rose during storage [38] and could relate to differences between the two rocket salad species. The differential changes in response to the different stress treatments is consistent with the subtle changes induced by storage at different temperatures [11] and effects of wounding on the release of VOCs [20,39].…”
Section: Discussioncontrasting
confidence: 99%
“…In disagreement with our work, a recent study performed on accessions of Eruca sativa [ 40 ] indicated that no significant correlation was found between GRA and GER. Furthermore, no significant correlations were observed for these GLs with any sensory attribute.…”
Section: Resultscontrasting
confidence: 99%
“…While genetic factors determining mainly the type of GSL, environmental factors influence the amount of them. The induction of GSL following abiotic or biotic stresses has frequently been described in order to increase the phytochemicals levels when GSL are hydrolyzed by myrosinase (thioglucoside glucohydrolase, EC 3.2.1.147) upon tissue disruption, numerous breakdown products are formed, including isothiocyanates (ITCs), thiocyanates, nitriles, ascorbigen, indoles, oxazolidine-2-thiones, and epithioalkanes depending upon different factors like pH, temperature, presence of myrosinase-interacting protein, and availability of ferrous ion [21]. Among the different GLS-degradation products formed, the most abundantly formed at physiological pH are the ITCs, which are also considered the main responsible for cruciferous foods bioactivity.…”
Section: Organosulfur Compoundsmentioning
confidence: 99%